Experience and Expectation of International Students: Over Barclays Bank, Service Quality in Chester, UK - Yeoward, Ms Joyce; Ashwathnarayana, Mr Prapul Kumar (International Journal of Scientific Research and Management (IJSRM), 2018)
In the 21stcentury service industry has grabbed and changed the phenomenal look of the business market, as service is an endless endeavor of any product, which is delivered as soon the product is launched in the market, and people are more depended on services, which has become an essential needs for them. When service is delivered to the customer the services providers’ has to maintain the quality of services, which might be beyond the expectation of the consumers, which will lead in a better level of satisfaction and elevate the organizations reputation. In the banking sector the main expectation of the customers is assurance, reliability, responsiveness taken by the bank, if the consumers are pleased by the services, then the bank accomplishes the purpose of satisfying the customer and delivering all their needs. In this research the researcher has considered the aspects of satisfying the expectations of customer, through the values of services quality and to understand the gap between experience and expectation by adopting SERVQUAL model and gap analysis, these helped the researcher to showcase the services quality provided by the Barclays bank Chester to the international students. By adopting the above model the researcher has conferred that the services provided by the Barclays bank has tried to satisfy the customer and the overall gap of expectation and satisfaction has showed positive score of (+ 2.26) this also describes that by providing more better and quality services, the customer satisfaction score can be improved. This also can be observed in future by carrying out other research programs on the same topic on larger demographic or international scale.